Criminal Sanctions of Chemical Elementary in the Perspective of Justice Principles - Kiki Kristanto; Mutia Evi Kristhy; Mandau Bakti; Jonson Jonson; Arif Irawan Sanjaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Sexual crime against children is a social phenomenon that is rife in Indonesia. This causes the government to be again required to formulate regulations to reduce the sensation of sexual crimes against children. Child protection activists are pushing for the castration of perpetrators of sexual crimes against children. The insistence on forming regulations related to castration is as if it is a cruel punishment aimed at perpetrators of sexual crimes against children. The question that arises from the discourse on the implementation of the castration sentence is, "Is the castration punishment by the principle of justice?".